Exploring everyday resilience in the creative industries through devised theatre: A case of performing arts students and recent graduates in Ghana - Resario, R.; Steedman, R.; Langevang, T. (International Journal of Cultural Studies, 2023)
The concept of resilience has become widely used to account for how people respond both to acute crises and, increasingly, to protracted precarity. Yet, cultural studies theorists have also vig orously critiqued resilience discourse as a tool of neoliberal governmentality. In this article, we turn from the discourse of resilience to the practice of resilience. We argue, through the case of theatre students and recent graduates in Ghana, that the practice of resilience can be both individual and collective. Moreover, we show that resilience practices involve the exercise of agency at various scales through the specific practices of coping, reworking, and resisting. Finally, we show the merits of using artistic research methods, such as devised theatre, to unveil the complex ways that creatives practice resilience in the everyday.
Research Article
Keywords: artistic research methods; creative industries; devised theatre